PENDIDIKAN AGAMA ALTERNATIF: STUDI KASUS SD AL-AZHAR YAYASAN HJ. RACHMAN NASUTION MEDAN (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
AbstractSome questions on educational system emerge, for example, education is not critical, not creative, excess burden of curriculum, boring, not recognizing participation, bank style, etc. this condition invites an initiative to organize the education according to their expectation which is different from the education organized conventionally. Relogious education as one of the pillars for the achievement of national educational objective can be positioned in the context of alternative education. One of those alternative religious educational organization is implemented by SD Al-Azhar Hajjah Rachmah Nasution Foundation, Medan.
Keywords: alternative education; alternative religious educational